Blockchain and the digital transformation of the public sector: The Greek experience - Xanthopoulou, Panagiota (Technium Social Sciences Journal, 2022)
The present study aims to investigate the key organizational factors that impact on the blockchain adoption in the Greek public sector during the current pandemic, which caused many changes in the ways that organizations operate and offer their services. A qualitative method was used through 78 structured interviews with public servants, regarding the digital transformation and the internal factors that hinder the successful integration of blockchain technologies during the current pandemic. The results showed that factors such as employees’ training, organizational culture and leadership, in addition to the lack of equipment, had great impact on the adoption and the successful integration of blockchain in the Greek public administration. Another crucial finding is that public servants consider the current pandemic as an opportunity and not as a threat for radical changes and improvements in the provision of their services, while they also stated that blockchain technologies can improve the ways that they provide public services to citizens and thus they will enhance the sense of public trust to public sector.